The Oxford Handbook of the Bible and the Reformation. Edited by Jennifer Powell McNutt and Herman J. Selderhuis. Oxford: Oxford University Press, 2024. xxvi + 748 pp. $ 190.00 cloth - Rittgers, Ronald K. (Church history, 2025)
The Oxford Handbook of the Bible and the Reformation. Edited by Jennifer Powell McNutt and Herman J. Selderhuis. Oxford: Oxford University Press, 2024. xxvi + 748 pp. $ 190.00 cloth - Volume 94 Issue 2